2016
DOI: 10.1371/journal.pone.0162480
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Men for “Low Testosterone”: A Systematic Review

Abstract: Testosterone products are recommended by some prescribers in response to a diagnosis or presumption of “low testosterone” (low-T) for cardiovascular health, sexual function, muscle weakness or wasting, mood and behavior, and cognition. We performed a systematic review of 156 eligible randomized controlled trials in which testosterone was compared to placebo for one or more of these conditions. We included studies in bibliographic databases between January 1, 1950 and April 9, 2016, and excluded studies involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 177 publications
0
63
0
1
Order By: Relevance
“…A recent review considered 48 studies assessing sexual function or libido as a primary or secondary endpoint of TTh [16]. The authors concluded that TTh did not show consistent benefit for sexual function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review considered 48 studies assessing sexual function or libido as a primary or secondary endpoint of TTh [16]. The authors concluded that TTh did not show consistent benefit for sexual function.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that TTh did not show consistent benefit for sexual function. However, that review failed to distinguish between results in eugonadal and E U R O P E A N U R O L O G Y X X X ( 2 0 1 7 ) X X X -X X X hypogonadal men, men with or without baseline symptoms, and studies that used different instruments for assessment [16]. In addition, their interpretation of results was not based on any stated criteria or validated statistical method, and relied solely on their personal interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found conflicting data, and recently, Huo et al . reviewed 156 eligible studies concluding that use of TRT to improve sexual function was without support from clinical trials (Gianatti et al ., ; Huo et al ., ). Our study in men experiencing changes in sexual function following treatment offers further insight.…”
Section: Discussionmentioning
confidence: 97%
“…We read with interest the systematic review (SR) by Huo et al [1] on the role of testosterone replacement therapy (TRT) for treating men with low testosterone, which suggests that there is no beneficial effect in most men. While we cannot rule out that the author's conclusions will ultimately be proven to be true, we believe that it is premature to make this determination based on the current study.…”
mentioning
confidence: 99%